PEMERIKSAAN REFRAKSI SUBYEKTIF PENDERITA PRESBYOPIA STATUS REFRAKSI ANTIMETROPIA BALAI KESEHATAN INDERA MASYARAKAT - Desy Ayu Pertiwi; Wahjoe Handini; Joko Sulistyo (EMVIRO Jurnal Ilmiah Penelitian Kesehatan, 2022)
Abstract Antimetropia is a condition in which a person with visual impairment has different refraction status. One of his eyes had myopia status and the other had hypermetropia status. Myopia is a state where the incoming rays are refracted from falling in the retina but in front of the retina. Hypermetropia is a state where the incoming rays are refracted not falling on the retina but behind the retina. Giving goggles to young age antimetropia sufferers will not cause a problem, because a single vision glasses can be used for remote viewing and reading. an elderly antimetropia patient, need to consider the additional size for his reading glasses in connection with presbyopia. This type of research is a qualitative research conducted by descriptive method, and research design using case study approach by performing direct examination with antimetropia sufferer. The sampling technique in this research is by purposive sample technique with criterion were patients aged over 40 years who have a unique refractive eye disorder status, where one eye is a myopia status while the other eye hypermetropia refractive status. The resulth of research in obtaining subjective refractive examination data of 500 people, most of the female of 326 people(65,2%), aged ≥ 40 years number of 258 people(51,6%). Of the total number of refractive examination subjects as many as 7 people(1,4%) suffering presbyopia with antimetropia refraction status. Keywords : Antimetropia, Presbyopia, Subjective Refraction Examination Abstrak Antimetropia merupakan suatu keadaan dimana seorang penderita gangguan penglihatan memiliki status refraksi yang berbeda, salah satu matanya berstatus myopia dan mata satunya berstatus hypermetropia. Myopia merupakan keadaan dimana sinar-sinar yang datang dibiaskan tidak jatuh di retina melainkan didepan retina. Hypermetropia merupakan keadaan dimana sinar-sinar yang datang dibiaskan tidak jatuh di retina melainkan di belakang retina. Pemberian kacamata pada penderita antimetropia usia muda tidak akan menimbulkan satu permasalahan, karena satu kacamata single vision sudah dapat dipergunakan untuk melihat jauh dan membaca, namun untuk penderita antimetropia usia tua, perlu mempertimbangkan ukuran tambahan untuk kacamata bacanya sehubungan dengan adanya presbyopia. Jenis penelitian ini penelitian kualitatif dengan metode deskriptif,. Teknik pengambilan sampel pada penelitian ini yaitu teknik purposive sampel dengan kriteria pasien yang berusia diatas 40 tahun yang memiliki kelainan status refraksi mata yang unik, dimana salah satu matanya berstatus myopia sedangkan mata yang lain berstatus refraksi hypermetropia. Hasil penelitian pemeriksaan refraksi subyektif sejumlah 500 orang, berjenis kelamin perempuan sejumlah 326 orang (65,2%), berumur ≥ 40 tahun sejumlah 258 orang(51,6%). Jumlah hasil pemeriksaan refraksi subyektif tersebut sebanyak 7 orang (1,4%) menderita presbyopia dengan status refraksi antimetropia. Kata kunci : Pemeriksaan Refraksi Subyektif, Presbyopia, Antimetropia